Diskresi Penyidik Polri Sebagai Alternatif Penanganan Perkara Pidana - Alfano Ramadhan (Lex Renaissance, 2021)
The purpose of this study is to identify, first, the application of investigator discretion at the Sleman Police in handling criminal acts as an effort to realize restorative justice. Second, the procedures for police investigators in exercising discretion as an effort to realize restorative justice. Third, the legal consequences of the discretion exercised by Polri investigators in the process of handling criminal cases. This study uses normative legal research with statutory and conceptual approaches. The results of this study conclude that first, the factors that encourage the investigative team to use their discretionary authority within the Sleman Police are the substance of the legislation; instructions from the Leader; investigators as law enforcers; as well as the situation and conditions in the investigation process. The external factor is the support from the community. Second, the application of discretion through a restorative justice approach changes the pattern of settlement to the needs of victims and improving public order compared to criminalizing someone. Third, the legal consequences that arise are that the rule of law is no longer the main choice in resolving cases in law enforcement efforts, this is due to the rule of law that does not fully accommodate the efforts to settle cases.Key Words: Discretion; police examiners; restorative justiceAbstrakTujuan dari penelitian ini adalah untuk mengetahui, pertama, penerapan diskresi penyidik di Polres Sleman dalam penanganan tindak pidana sebagai upaya mewujudkan restorative justice. Kedua, prosedur penyidik Polri dalam melakukan diskresi sebagai upaya mewujudkan restorative justice. Ketiga, akibat hukum atas diskresi yang dilakukan oleh penyidik Polri terhadap proses penanganan perkara pidana. Penelitian ini menggunakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil dari penelitian ini menyimpulkan bahwa pertama, faktor yang mendorong tim penyidik dalam menggunakan wewenang diskresinya di lingkungan Polres Sleman adalah substansi perauran perundang-undangan; instruksi dari pimpinan; penyidik selaku penegak hukum; serta situasi dan kondisi dalam proses penyidikan. Faktor eksternal yaitu adanya dukungan dari masyarakat. Kedua, penerapan diskresi melalui pendekatan restorative justice merubah pola penyelesaiannya pada kebutuhan korban dan perbaikan ketertiban masyarakat dibandingkan dengan memidanakan seseorang. Ketiga, akibat hukum yang timbul adalah aturan hukum bukan lagi menjadi pilihan utama dalam penyelesaian perkara dalam upaya penegakan hukum, hal tersebut dikarenakan aturan hukum yang tidak sepenuhnya mengakomodir dalam upaya penyelesaian perkara.Kata Kunci: Diskresi; restorative justice; penyidik polisi